TENDÊNCIAS DO ENSINO DE LITERATURA NAS LICENCIATURAS EM LETRAS - Furtado, Caio Augusto Martins [UNESP]; Annibal, Sérgio Fabiano [UNESP] (Revista Ibero-Americana de Estudos em Educacao, 2024)
This article, through documentary research and analysis of Teaching Plans (PE) of Bachelor's degrees in Languages and Literature of public universities, aims to enter the conceptions of literature teaching adopted in teacher education. Thus, this investigation is positioned in order to understand how the field of Literature understands the teaching of literature and how these pedagogical documents can shape the education of teachers in the area, based on different theoretical-methodological conceptions. The objective of this article is, therefore, to identify and classify the trends that emerge from the analyzed documents, in order to better visualize the functioning of the Literature and Education interface. Among the results, three tendencies and a transversal element, common to all categories, are characterized. As final remarks, the authors emphasize the importance of the analysis undertaken to elucidate the internal logics of the educational and language fields, and their possible resonances from teacher education.